Assessing the impact of sulfur concentrations on growth and biochemical composition of three marine microalgae - Fernandes, Tomásia (2021)
The elemental stoichiometry, growth and biochemical composition of Nannochloropsis gaditana, Rhodomonas marina and Isochrysis sp. were studied in batch cultures against different nitrogen and sulfur molar ratios (N:S) imposed in their surroundings. In N. gaditana, treatments with low N:S lead to an increase in carbon:sulfur (C:S) and N:S molar ratios up to 95 and 81%, respectively. This was reflected in lipid and protein contents which increased up to 67 and 55%, respectively. Moreover, polyunsaturated fatty acids, as well as its precursors, increased in low N/S treatments. In R. marina, the treatments applied promptly the decrease of both C:S and N:S ratios to 70 and 68%, respectively. Nevertheless, eicosapentaenoic:arachidonic acid ratio increased with N:S treatments by three and a half fold. In Isochrysis sp., the elemental stoichiometry was constrained against treatments until the highest sulfur input. Overall, sulfur supply highlighted microalgae taxonomic differences and suggested that biochemical control is required, even in nutrient replete conditions, to fully exploit their potential as added value biomachineries.